2010
DOI: 10.1007/s12640-010-9216-9
|View full text |Cite
|
Sign up to set email alerts
|

Thioperamide, an H3 Receptor Antagonist Prevents [3H]Glucose Uptake in Brain of Adult Rats Lesioned as Neonates with 5,7-Dihydroxytryptamine

Abstract: As a first attempt at exploring an association between histaminergic and serotoninergic neuronal phenotypes in glucose regulation, the influence of the histamine H₃ receptor antagonist thioperamide on glucose uptake by brain was determined in rats in which the serotoninergic innervations of brain was largely destroyed perinatally. Male Wistar rats were initially treated on the 3rd day after birth with the serotoninergic neurotoxin 5,7-dihydroxytryptamine (5,7-DHT) (75 μg icv) or saline vehicle (10 μl icv). At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Other studies demonstrated that H2 blockers are potent scavengers of ROS produced by inflammatory cells, such as neutrophils [ 18 , 19 ]. On the other hand, cimetidine administered to patients with peptic ulcers and healthy subjects increased • O 2 − production in granulocytes, whereas ranitidine and famotidine did not elicit such a response [ 20 ]. In view of the contradictory reports on the antioxidant properties of H2 antagonists and a general scarcity of research on their effects on carbonyl stress, the present study was undertaken to investigate the anti-glycoxidant properties of these pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrated that H2 blockers are potent scavengers of ROS produced by inflammatory cells, such as neutrophils [ 18 , 19 ]. On the other hand, cimetidine administered to patients with peptic ulcers and healthy subjects increased • O 2 − production in granulocytes, whereas ranitidine and famotidine did not elicit such a response [ 20 ]. In view of the contradictory reports on the antioxidant properties of H2 antagonists and a general scarcity of research on their effects on carbonyl stress, the present study was undertaken to investigate the anti-glycoxidant properties of these pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%